Urban economics - O'Sullivan, Arthur (Boston, Mass.: McGraw-Hill/Irwin, 2007)
The book uses economic analysis to explain why cities exist, where they develop, how they grow, and how different activities are arranged within cities.
Includes bibliographical references and index.
lje 5/9/13
Loans
Keywords: Urban economics